The transporter [videorecording (DVD)] - Besson, Luc; Kamen, Robert Mark; Statham, Jason, 1967-; Shu, Qi, 1976-; Berléand, François; Schulze, Matt; Young, Ric (20th Century Fox Home Entertainment, 2003)
Frank Martin (Jason Statham) is the best at what he does -- transporting dangerous or illegal goods with no questions asked. But his latest shipment, a beautiful young woman kidnapped by slave traders, brings deadly complications to his delivery plans. Frank must kick into overdrive and fight to save his cargo, and his life.